Description of Paraclytus xiongi sp. nov. from Yunnan, China (Coleoptera: Cerambycidae: Cerambycinae: Anaglyptini) - Huang, Gui-Qiang; Yan, Kai; Zhang, Gui-Mei (Zootaxa, 2020)
Paraclytus xiongi sp. nov. is described from Yunnan, China. Habitus of adults, hind wings, male terminalia and intraspecific variation of Paraclytus xiongi sp. nov. are illustrated. The differences between Paraclytus xiongi sp. nov. and related species are provided.